A Nanoemulsion with A Porphyrin Shell for Cancer Theranostics. (5th September 2019) - Hou, Wenxiu; Lou, Jenny W. H.; Bu, Jiachuan; Chang, Enling; Ding, Lili; Valic, Michael; Jeon, Han Ho; Charron, Danielle M.; Coolens, Catherine; Cui, Daxiang; Chen, Juan; Zheng, Gang
Abstract: A nanoemulsion with a porphyrin shell (NewPS) was created by the self‐assembly of porphyrin salt around an oil core. The NewPS system has excellent colloidal stability, is amenable to different porphyrin salts and oils, and is capable of co‐loading with chemotherapeutics. The porphyrin salt shell enables porphyrin‐dependent optical tunability. The NewPS consisting of pyropheophorbide a mono‐salt has a porphyrin shell of ordered J‐aggregates, which produced a narrow, red‐shifted Q‐band with increased absorbance. Upon nanostructure dissociation, the fluorescence and photodynamic reactivity of the porphyrin monomers are restored. The spectrally distinct photoacoustic imaging (at 715 nm by intact NewPS) and fluorescence increase (at 671 nm by disrupted NewPS) allow the monitoring of NewPS accumulation and disruption in mice bearing KB tumors to guide effective photodynamic therapy. Substituting the oil core with Lipiodol affords additional CT contrast, whereas loading paclitaxel into NewPS facilitates drug delivery. Abstract : Shell Oil Co .: Eine stabile Zweikomponenten‐Nanoemulsion mit einer Porphyrinhülle (NewPS) wurde für die multimodale Krebserkennung, Phototherapie und bildgebungsgesteuerte Wirkstoffabgabe entwickelt.